Electrochromic Device Composed of a Di-Urethanesil Electrolyte Incorporating Lithium Triflate and 1-Butyl-3-Methylimidazolium Chloride - Gonçalves, Maria Cristina; Pereira, Rui F. P.; Alves, Raquel; Nunes, Sílvia C.; Fernandes, Mariana; Gonçalves, Helena M. R.; Pereira, Sónia; Silva, M. Manuela; Fortunato, Elvira; Rego, Rosa; de Zea Bermudez, Verónica (Frontiers in Materials, 2020)
A di-urethane cross-linked poly(oxyethylene)/silica hybrid matrix (di-urethanesil, d-Ut(600)), sinthesized by the sol-gel process, was doped with lithium triflate (LiCF3SO3) and the 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) ionic liquid. The as-produced xerogel film is amorphous, transparent, flexible, homogeneous, hydrophilic, and has low nanoscale surface roughness. It exhibits an ionic conductivity of 3.64×10−6 and 5.00×10−4 S cm-1 at 21 and 100 ºC, respectively. This material was successfully tested as electrolyte in an electrochromic device (ECD) with the glass/ITO/a-WO3/d-Ut(600)10LiCF3SO3[Bmim]Cl/c-NiO/ITO/glass configuration, where a-WO3 and c-NiO stand for amorphous tungsten oxide and crystalline nickel oxide, respectively. The device demonstrated attractive electro-optical performance: fast response times (1-2 s for coloring and 50 s for bleaching), good optical memory (loss of transmittance (T) of only 41% after three months, at 555 nm), four mode modulation (bright mode (+3.0 V, T = 77% at 555 nm), semi-bright mode (−1.0 V, T = 60% at 555 nm), dark mode (−1.5 V, T = 38 % at 555 nm), and very dark mode (−2.0 V, T = 11% and −2.5 V, T = 7% at 555 nm )), excellent cycling stability denoting improvement with time, and high coloration efficiency (CEin = −6727 cm2 C−1 (32th cycle) and CEout = +2794 cm2 C−1 (480th cycle), at 555 nm).